Pengaruh Parent Teach Program Terhadap Motivasi Belajar Siswa di SD Khazanah Ilmu Taman Sidoarjo - Rahmawati, Laili; Taufik, Taufik; Mas’ud, Sulthon; Nadlir, Nadlir; Fuad, Nasrul (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
The lack of motivation that students have in learning will have an impact on whether or not the learning objectives will be achieved effectively. Students' learning motivation will be well formed if there is a good role of parents and teachers too. The role of parents in learning is a factor in the formation of motivation. The Parent Teach Program is a school program that involves parents in the learning process. The aim of this research is to determine the effect of the Parent Teach Program on student learning motivation at Khazanah Ilmu Elementary School, Taman Sidoarjo. This Quantitative Research uses a Survey Method with a Descriptive approach. Random sampling technique (random sampling). The sample for this research was 55 students in grades III, VI, V, and VI. Data collection techniques use observation, interviews and questionnaires. Data analysis uses three tests, namely Validity and Reliability Instrument Test, Analysis Prerequisite Test (normality and linearity), and Hypothesis Test (Product Moment Correlation). The results of the research show that the perceptions of class III, IV, V, and VI students regarding the influence of the Parent Teach Program on learning motivation are in the positive and influential category. This is shown by the results of the analysis using product moment correlation, which obtained Asymp.Sig = 0.00 (0.00 < 0.05) and the correlation value with a calculated r value of 0.628 > r table of 0.266, it can be concluded that H0 is rejected and Ha is accepted. The results of this research are positively and significantly correlated and are categorized as a strong relationship that there is an influence between the Parent Teach Program and student learning motivation. The influence of the Parent Teach Program on students' learning motivation in classes III, IV, V and VI at SD Khazanah Ilmu, Taman Sidoarjo was 39.4%.